The Use of Motivation Video “The Gift” & Student Critical Thinking toward Listening Skills of Tenth Grade of SMA Srijaya Negara - Putra, Rian Pratama (Universitas Batanghari Jambi, 2024)
This study aims to initiate the effectiveness of the use of the motivational video